The mysterious Benedict Society - Stewart, Trenton Lee.; Ellis, Carson, 1975- (New York : Little, Brown, 2007)
After passing a series of mind-bending tests, four children are selected for a secret mission that requires them to go undercover at the Learning Institute for the Very Enlightened, where the only rule is that there are no rules.
"Megan Tingley books."
Booklist starred.
Horn Book.
Pub Weekly.
6.4
3-6
Keywords: Adventure and adventurers -- Fiction; Schools -- Fiction; Science fiction; Adventure fiction; School stories; Science fiction